DIFFERENCE IN CORRECT KICKING OF THE SOCCER BALL WITH RESTED WEEK LEG EXPRESSED WITH DIFFERENT INTENSITY - Duško Bjelica (Sport Scientific And Practical Aspects, 2025)
(This sample is valid only for research where 3 and 4 variables were treated) Group of young soccer professionals was hitting goal in the same way from the same distance. Each respondent kicked with both legs for ten times. In the first case the kick was performed with rested week leg with optimal intensity for 10 times, and after special program of relaxation in order to let them rest the muscles that are engaged the most in kicking the ball, other 10 kicks was performed with rested strong leg with maximal intensity. After statistic procedure processing, we determined that maximal intensity significantly influenced decrease in accuracy of hitting goal, which confirmed criteria hypothesis.